2021
DOI: 10.1101/2021.02.17.21251895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for long-term consequences of COVID-19 in hospitalised adults in Moscow using the ISARIC Global follow-up protocol: StopCOVID cohort study

Abstract: Background The long-term sequalae of COVID-19 remain poorly characterised. In this study, we aimed to assess long-standing symptoms (LS) (symptoms lasting from the time of discharge) in previously hospitalised patients with COVID-19 and assess associated risk factors. Methods This is a longitudinal cohort study of adults (18 years of age and above) with clinically diagnosed or laboratory-confirmed COVID-19 admitted to Sechenov University Hospital Network in Moscow, Russia. Data were collected from patients di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
36
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 19 publications
11
36
0
3
Order By: Relevance
“…Our results are consistent with a recent report of non-hospitalized COVID-19 patients, where 55% had at least one persisting symptom at six months follow-up, and persisting symptom severity was dependent on disease severity [ 6 ]. Our main finding, that a significant proportion of COVID-19 patients do not recover completely after three to eight months is also consistent with unpublished surveys without control groups in non-hospitalized and hospitalized patients [ 5 , 16 , 17 ]. These surveys also describe a possible long-COVID syndrome that include cognitive symptoms not covered in our questionnaires, which may serve to explain why our COVID-19 patients reported a worsening of health while their burden of airway symptoms at follow-up was lower than the controls.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with a recent report of non-hospitalized COVID-19 patients, where 55% had at least one persisting symptom at six months follow-up, and persisting symptom severity was dependent on disease severity [ 6 ]. Our main finding, that a significant proportion of COVID-19 patients do not recover completely after three to eight months is also consistent with unpublished surveys without control groups in non-hospitalized and hospitalized patients [ 5 , 16 , 17 ]. These surveys also describe a possible long-COVID syndrome that include cognitive symptoms not covered in our questionnaires, which may serve to explain why our COVID-19 patients reported a worsening of health while their burden of airway symptoms at follow-up was lower than the controls.…”
Section: Discussionsupporting
confidence: 91%
“…PASC may be found to affect a high proportion of people who had mild cases of COVID-19, and there is an urgent need for a detailed description of PASC in nonhospitalized patients. 2 , 3 This cohort study examines self-reported memory problems 8 months after COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients who survive acute-Covid-19 experience persistent symptoms beyond 4 weeks, known as 'long-Covid' 8 . This includes a wide range of symptoms, such as breathlessness, fatigue, muscle pain, many of which overlap with PICS and other post-viral syndromes 1,[9][10][11][12][13][14][15][16] . The most common symptom of long-Covid described following both community and hospital-managed acute-Covid-19 was fatigue: fatigue was reported in 97.7% of community-managed cases who reported symptoms lasting over 28 days, and in 83% and 98% of UK and China patients respectively greater than 3-months after hospital discharge following admission with acute-Covid-19 11,16,17 .…”
Section: Introductionmentioning
confidence: 99%